2020
DOI: 10.1093/ndt/gfaa232
|View full text |Cite
|
Sign up to set email alerts
|

Does dietary potassium intake associate with hyperkalemia in patients with chronic kidney disease?

Abstract: Background Dietary potassium restriction is a strategy to control hyperkalemia in chronic kidney disease (CKD). However, hyperkalemia may result from a combination of clinical conditions. This study aimed to investigate whether dietary potassium or the intake of certain food groups associate with serum potassium in the face of other risk factors. Methods We performed a cross-sectional analysis including a nondialysis-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 34 publications
5
79
0
9
Order By: Relevance
“…The lack of association disclosed by the mixed effect analysis further confirms that K intake does not play a major role in the control of chronic HK in ND-CKD patients because of the predominant role of low GFR, acidosis and RAASI in these patients. This finding supports the results of previous studies in non-dialysis and dialysis CKD showing a dissociation between sK and potassium intake when estimated on the basis of food questionnaires [40]. It is important to note, however, that factors other than dietary intakes, such as gastrointestinal potassium secretion, or the effect of potassium binders and loop diuretics, that are common treatment options among CKD patients, could induce modifications in the amount of potassium absorbed in the bowel and/or urinary potassium elimination [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…The lack of association disclosed by the mixed effect analysis further confirms that K intake does not play a major role in the control of chronic HK in ND-CKD patients because of the predominant role of low GFR, acidosis and RAASI in these patients. This finding supports the results of previous studies in non-dialysis and dialysis CKD showing a dissociation between sK and potassium intake when estimated on the basis of food questionnaires [40]. It is important to note, however, that factors other than dietary intakes, such as gastrointestinal potassium secretion, or the effect of potassium binders and loop diuretics, that are common treatment options among CKD patients, could induce modifications in the amount of potassium absorbed in the bowel and/or urinary potassium elimination [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Further, higher dietary intake of K is associated with better blood pressure control and lower risk of ischemic stroke [39-41]. However, current guidelines recommend restriction of dietary intake of K due to the risk of hyperkalemia [42], despite the lack of association between dietary K intake and serum K levels or hyperkalemia [43] and the known health benefits of high dietary K intake [2]. However, lack of dietary K intake data did not allow us to assess the association of dietary intake of K (in concurrence with serum K) with ischemic stroke.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Excessive limitation of potassium intake may lead to hypokalemia [20] , malnutrition [21] , and increased risk of poor prognosis [22] . However, a study showed a controversial finding that dietary potassium was not associated with serum potassium levels [23] . Nonetheless, it has been demonstrated that patients with higher RAAQ scores are at a lower risk of all-cause mortality from CKD [24] .…”
Section: The Impacts Of Diuretics Raas Indicators and Low Raaq Scorementioning
confidence: 99%